Nutrient Intake from Fortified Foods and Supplements in Vegan, Vegetarian, and Omnivorous Participants Aged 6 to 18 Years in Germany: Results from the VeChi Youth Study - Joelina Dietrich; Vanessa Keller; Morwenna Fischer; Stine Weder; Ute Alexy; Andreas Michalsen; Alfred Längler; Andreas Sputtek; Markus Keller (Proceedings)
Introduction: The German market for dietary supplements and fortified foods is of considerable size, and many target-group-specific products, e.g., for vegans and vegetarians, are available. Growing sales volumes in recent years reflect the large demand for these products. However, the broad variety and easy availability may lead to unfavorable use of these products. Methods: The VeChi Youth Study (2017–2019) was a cross-sectional study among vegan (VN), vegetarian (VG), and omnivorous (OM) participants aged 6 to 18 years (n = 401). Dietary data were collected from 3-day weighed dietary records (n = 390). The present analysis investigates nutrient intake from dietary supplements and unfortified/fortified foods. Results: VN had the highest dietary supplement use and the highest intake of fortified foods (both significantly different from OM; p < 0.0001 and p = 0.0342, respectively). Among VN and VG, vitamins B12 and D were the most frequently supplemented nutrients, while among OM, this was vitamin C. The mean nutrient intake from dietary supplements (excluding vitamins B12 and D) and fortified foods contributed up to 49% and 11% of the German reference values, respectively. Except for iron, VN had the highest mean intake of all nutrients from dietary supplements. Including unfortified and fortified foods as well as supplements, the mean intake in all three diet groups reached the reference values for vitamin B12, vitamin C, iron, and zinc but not for calcium and iodine. Discussion: Dietary supplements, and to a smaller extent fortified foods, increased the nutrient intake of the participants of the VeChi Youth Study. In order to achieve recommended intakes, the intake of dietary supplements and fortified foods was either unnecessary (e.g., vitamin C), not sufficiently effective (e.g., calcium and iodine), or effective (e.g., vitamin B12). Conclusions: Specific intake of dietary supplements is useful to improve the intake of critical nutrients in VN and VG diets, especially for vitamins B12 and D. In Germany, fortified foods appear to contribute only to a small extent to the intake of critical nutrients in VN and VG children and adolescents.